The Implementation of School-Based Management (SBM) in Improving the Quality of Learning at MAN 1 Kota Sukabumi - Cecep Hilman; Irma Muti; Arfiani Yulianti Fiyul; Siti Rohmah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The quality of learning in madrasahs must continually be improved in response to increasingly complex educational demands. This study aims to describe the implementation of School-Based Management (SBM) in improving the quality of learning at MAN 1 Kota Sukabumi. The research method used is qualitative with a field research approach. The research instruments consisted of interview guides, observation sheets, and documentation. Data collection techniques were carried out through in-depth interviews with the principal, teachers, and the school committee; direct field observations; and document analysis. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results of the study indicate that SBM was implemented through the involvement of all school stakeholders in decision-making, improving teacher competence through training, optimizing learning facilities, and active parental involvement in supporting the learning process. The conclusion of this study shows that SBM plays a significant role in enhancing the quality of learning when implemented in a participatory and sustainable manner. Key Words: School-Based Management, Learning Quality, School Participation Abstrak (Indonesia): Mutu pembelajaran di madrasah perlu terus ditingkatkan seiring tuntutan pendidikan yang semakin kompleks. Penelitian ini bertujuan untuk mendeskripsikan implementasi Manajemen Berbasis Sekolah (MBS) dalam meningkatkan mutu pembelajaran di MAN 1 Kota Sukabumi. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan field research. Instrumen penelitian berupa pedoman wawancara, lembar observasi, dan dokumentasi. Teknik pengumpulan data dilakukan melalui wawancara mendalam dengan kepala madrasah, guru, dan komite, observasi langsung di lapangan, serta studi dokumentasi. Data dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi MBS dilakukan melalui pelibatan semua unsur madrasah dalam pengambilan keputusan, peningkatan kompetensi guru melalui pelatihan, optimalisasi sarana pembelajaran, serta keterlibatan aktif orang tua dalam mendukung proses belajar mengajar. Simpulan dari penelitian ini menunjukan bahwa MBS berperan signifikan dalam peningkatan mutu pembelajaran apabila dilaksanakan secara partisipatif dan berkelanjutan. Kata Kunci: Manajemen Berbasis Sekolah, Mutu Pembelajaran, Partisipasi Sekolah